5+6x-4=7x-4-4x

Simple and best practice solution for 5+6x-4=7x-4-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6x-4=7x-4-4x equation:


Simplifying
5 + 6x + -4 = 7x + -4 + -4x

Reorder the terms:
5 + -4 + 6x = 7x + -4 + -4x

Combine like terms: 5 + -4 = 1
1 + 6x = 7x + -4 + -4x

Reorder the terms:
1 + 6x = -4 + 7x + -4x

Combine like terms: 7x + -4x = 3x
1 + 6x = -4 + 3x

Solving
1 + 6x = -4 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + 6x + -3x = -4 + 3x + -3x

Combine like terms: 6x + -3x = 3x
1 + 3x = -4 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + 3x = -4 + 0
1 + 3x = -4

Add '-1' to each side of the equation.
1 + -1 + 3x = -4 + -1

Combine like terms: 1 + -1 = 0
0 + 3x = -4 + -1
3x = -4 + -1

Combine like terms: -4 + -1 = -5
3x = -5

Divide each side by '3'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| x^2-24x+40=0 | | a(x-5)=2b+7a | | 3x+15=2(-x) | | x^2-10-6x= | | 80=5(6+r) | | =48x^2-200x+200 | | 1=1-4x+4 | | m+12/9=5/9 | | m^2=-35+12m | | -5(2b+1)+(11b-6)=0 | | 97-13=-8(-4y)-17(2y)+y | | 12-4*3= | | x^2+10-6x= | | 0.15x+0.10(280-x)=30.75 | | y=-2(1)-5 | | 12-4.3= | | 3s=69 | | 3.3q-1.7-3.9q=-1.6q-1.7 | | .4(2x+4)=4.8 | | 45x^4+5x^2=0 | | 2x^2-6x+10= | | 2(x+4)-5=2*x+3 | | 4+6x+5=7x | | 2x=-21x+7 | | 1(x^2+x-30)=0 | | 27k=0 | | 2(x+3)(x-1)=c+176 | | 8(2x-4)=2(8x+9) | | 4x-36=-36+4x | | 3x=6x-1 | | 56+12n=80+8n | | 2+2n-6n=-6 |

Equations solver categories